The argument flagging and indexing construction in the Jewish Arabic dialect of Baghdad - Bar-Mosheh, Asaf (Journal of Semitic studies, 2021)
The Jewish dialect of Baghdad employs a particular construction to mark constituents of the clause as arguments. This construction typically marks the argument twice—once by the morpheme l‐ and once by a pronominal suffix that agrees with the argument. Syntactically, the former has the properties of a flag and the latter of a person index. The construction, which we call THE ARGUMENT FLAGGING AND indexing construction, primarily assigns the argument with the syntactic function of a direct or an indirect object, but it is also capable of marking oblique and genitive arguments. This paper focuses on the morpho‐syntactic properties of the construction. It presents the mechanism by which the argument is marked and describes how the syntactic function is assigned.